Problems with Greek clothing terminology - Richard, Quentin (Archaeological Textiles Review, 2021)
The Greek vocabulary of clothing and textile production is rich and varied. It contains hundreds of words that have survived in literary texts or in epigraphic resources. Ancient lexicographers attempted to compile these terms but the meaning of many of them has disappeared, only a few can be identified with certainty in visual representations. The clothing nomenclature used today was mainly established by German academics in the 19th century and has become widely adopted. However, modern studies show that some of these interpretations could be questioned. In this situation, what words should be used to designate Greek garments represented on artworks? There are different propositions: continue to use Greek terms conventionally or try to establish alternative nomenclature. In this paper it is argued that the use of modern generic terms could minimise problems of interpretation in the study of Greek clothing.